СОЦИОЛИНГВИСТИЧКИ АСПЕКТИ НА МАКЕДОНСКИОТ ЈАЗИК:ОД САТНДАРДИЗАЦИЈА ДО АКТУЕЛНИТЕ ТЕНДЕНЦИИ (Filološke studije, 2019)
The paper deals with various aspects relating to Macedonian: from a diachronic aspect the prestige of languages spoken in Macedonia through history shows a variety of languages which had prestige in the region - Greek, Latin, Serbo-Croatian, which had a significant impact on language development as well as the bilingualism and diglossia which were present in the course of several centuries. 2. The standardisation of Macedonian language is an important event regarding the Macedonian nation and state. Krste Misirkov with his work on recognition of Macedonian at the beginning of XXth century, and Blaze Koneski who made a great contribution with his work in the Commission for Literary Macedonian Language during 1944, are the two main figures in Macedonian linguistics concerning the standardisation process. 3. Regarding the status of Macedonian language today it should be pointed out that the change of Article 7 of the Constitution in 2002 has brought a new process in direction of granting an official language status for another language spoken by at least 20% of the population; this could be characterized as a situation which is one step away from bilingualism on the one hand, and on the other - there is a development of abandoning the concept of an official language as a cohesion factor in the country. The integrative role of official languages in European countries is a very common policy concept apart from respecting regional and minority languages, and it should be taken in regard when resolving the language/s status in Macedonia. 4. In reviewing the current linguistic tendencies it is unavoidable to consider the anglicisms in Macedonian used on different levels of language application. It is being viewed as a part of a global process relating to the presence of English as a lingua franca in almost every field of human interaction. 5. The processes regarding the languages in Europe include two developments: the official language status of one particular language vis-à-vis the respect for multilingualism in the European countries and promotion of minority language use. These two processes are not always compatible and they might lead to a situation where “the micronationalisms might diminish the importance of official languages”, as Calvet (2002: 185) is pointing out. In this context the language situation in Macedonia should be observed closely in regard to gaining balance between the official language/s and the rights as well as obligations of minority groups.